Finanzierungsstrukturen und makroökonomische Stabilität in den Ländern Südosteuropas, der Türkei und in den GUS-Staaten - Adalbert Winkler; Ursula Vogel (Frankfurt School of Finance & Management, 2009)
Within the last decade sizeable capital inflows from mature economies were accompanied by rapid financial deepening in the Western Balkans, Turkey and the CIS. Notwithstanding their considerably different initial positions most countries sustained financial stability in the first period of the financial crisis. But after the failure of Lehman Brothers neither the strategy of inviting fit and proper foreign banks nor the strategy of self-protection via current account surpluses and foreign exchange reserve accumulation provided a guarantee for macroeconomic stability. Thus, the experience of the region provides another example for the need of a multilateral strategy for financial integration and globalization to ensure the stability of the international financial system.
Keywords: F33; F34; F36; G21; O16; 330; Financial structure; financial integration; credit growth; financial crisis